The Effect of Feeding Red Bean Ice Cream on Weight Increasing Wasting Toddler in the Working Area of the Kawalu Health Center - Mulyana, Asep; Luthfi, Baharudin; Aguspita Dewi, Heni; Ulfah Jamil, Maria (Nurul Ilmi : Journal of Health Sciences and Midwifery, 2024)
Introduction: One of the SDGs targets is that by 2030 all countries will strive to reduce the under-five mortality rate by 25/1,000 live births. In addition to the 2030 public nutrition target, all countries are working to end all forms of malnutrition, including achieving the 2025 international target which aims to reduce stunting and wasting in children under five and address the nutritional needs of adolescent girls, pregnant and breastfeeding women, as well as elderly. Malnutrition will have a negative impact on physical and mental growth which will then hinder learning achievement. During the toddler years, the growth and development of brain cells is so rapid that they require optimal and optimal nutritional intake and stimulus. Toddlers are vulnerable to nutritional disorders because at this time they need nutrition for their growth and development. Apart from that, toddlers are very passive regarding food intake so that toddlers will depend on their parents. Objective: The aim of this research was to determine the effect of giving red bean ice cream on increasing the weight of wasting toddlers. Method: This research is quantitative research, with a pre-experimental design method using a one group pretest posttest design approach. The sample in this study was 15 toddlers who experienced wasting. Result: The results of this study indicate that there is an influence of red bean ice cream on weight gain in wasting toddlers. Conclusion: Based on the research results obtained, there is an effect of giving red bean ice cream on increasing the weight of wasting toddlers.